The Impact of Creativity and Innovation of Human Resources on the Quality of Service provided at the Middle Technical University - Batool Shamran Al-Saadi; Dr. Elie Maroun EL Hokayem (المجلة الدولية للعلوم الإنسانية والاجتماعية)
The study aimed to identify the impact of creativity and innovation of human resources on the quality of service provided through a sample of workers at the Central Technical University. For this purpose, the researcher used the questionnaire to collect data and information, and the researcher adopted a random sample of (372) individuals. The analytical descriptive approach was used, and the data were processed by the statistical software package for social sciences (SPSS). Using appropriate statistical methods such as the arithmetic mean, standard deviation, and Pearson's correlation to determine the relationship between the independent variables represented by creativity and innovation and the dependent variable represented by the quality of service provided by the Central Technical University, Cronbach's alpha coefficient was used for reliability. The study concluded that there is a statistically significant relationship between creativity, innovation and the quality of service provided at the Central Technical University. From this relationship, the study concluded that there is an impact of creativity and innovation on the quality of service provided at the university, and that (78.3%) of changes in the quality of service provided at the university are explained by creativity. And innovation, the study also found that the level of creativity and innovation in the university was low, and that the level of quality of service provided at the university was low too. This study also concluded with a set of recommendations, including; the objectives of the curricula must take into account the needs of students, the labor market, the knowledge society, and the nature of the era, as well as setting clear mechanisms that enable new students to see the nature and requirements of the programs they wish to join.